Color of Artificial Light at Night Affects Incubation Behavior in the Great Tit, Parus major - van Dis, Natalie E.; Spoelstra, Kamiel; Visser, Marcel E.; Dominoni, Davide M. (Frontiers in Ecology and Evolution, 2021)
Artificial light at night (ALAN) has been recognized as a biodiversity threat due to the drastic effects it can have on many organisms. In wild birds, artificial illumination alters many natural behaviours that are important for fitness, including chick provisioning. Although incubation is a key determinant of the early developmental environment, studies into the effects of ALAN on bird incubation behaviour are lacking. We measured nest temperature in nest boxes of great tits during the incubation period in two consecutive years. Nest boxes were located in eight previously dark field sites that have been experimentally illuminated since 2012 with white, green, or red light, or were left dark. We tested if light treatment affected mean nest temperature, number of times birds leave the nest (off-bout frequency), and off-bout duration during the incubation period. Subsequently, we investigated if incubation behaviour is related to fitness. We found that birds incubating in the white light during a cold, early spring had lower mean nest temperatures at the end of incubation, both during the day and during the night, compared to birds in the green light. Moreover, birds incubating in white light took fewer off-bouts, but off-bouts were on average longer. The opposite was true for birds breeding in the green light. Low incubation temperatures and few but long off-bouts can have severe consequences for developing embryos. In our study, eggs from birds that took on average few off-bouts needed more incubation days to hatch compared to eggs from birds that took many off-bouts. Nevertheless, we found no clear fitness effects of light treatment or incubation behaviour on the number of hatchlings or hatchling weight. Our results add to the growing body of literature that shows that effects of ALAN can be subtle, can differ due to the spectral composition of light, and can be year-dependent. These subtle alterations of natural behaviours might not have severe fitness consequences in the short-term. However, in the long term they could add up, negatively affecting parent condition and survival as well as offspring recruitment, especially in urban environments where more environmental pollutants are present.